2007
DOI: 10.1136/gut.2006.100164
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition and development of atopic manifestations in infancy: the KOALA Birth Cohort Study

Abstract: Background and aims: Perturbations in intestinal microbiota composition due to lifestyle changes may be involved in the development of atopic diseases. We examined gut microbiota composition in early infancy and the subsequent development of atopic manifestations and sensitisation. Methods: The faeces of 957 infants aged 1 month and participating in the KOALA Birth Cohort Study were analysed using quantitative real-time PCR. Information on atopic symptoms (eczema, wheeze) and potential confounders was acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
600
2
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(642 citation statements)
references
References 60 publications
16
600
2
24
Order By: Relevance
“…The stools of atopic subjects had more clostridia and tended to have fewer bifidobacteria than those of non atopic subjects, resulting in a reduced ratio of bifidobacteria to clostridia (Kalliomaki et al, 2001a). The Koala Birth Cohort Study in the Netherlands confirmed these results by showing that gut dysbiosis precedes the manifestation of atopic symptoms and atopic sensitization (Penders et al, 2007). In particular, C. difficile was associated with all atopic symptoms and sensitization.…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiessupporting
confidence: 70%
See 2 more Smart Citations
“…The stools of atopic subjects had more clostridia and tended to have fewer bifidobacteria than those of non atopic subjects, resulting in a reduced ratio of bifidobacteria to clostridia (Kalliomaki et al, 2001a). The Koala Birth Cohort Study in the Netherlands confirmed these results by showing that gut dysbiosis precedes the manifestation of atopic symptoms and atopic sensitization (Penders et al, 2007). In particular, C. difficile was associated with all atopic symptoms and sensitization.…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiessupporting
confidence: 70%
“…As E. coli was only associated with eczema and C. difficile was associated with all atopic outcomes, the underlying mechanisms may be different. Colonization with clostridia, including C. difficile, was associated with allergy development up to age 2 years in several studies (Kalliomaki et al, 2001a;Bjorksten et al, 2001;Penders et al, 2007) but not in others (Adlerberth et al, 2007;Sjogren et al, 2009;Songjinda et al, 2007). Fecal colonization at age 3 weeks with Clostridium coccoides subcluster XIVa species has been described as an early indicator of possible asthma later in life Vael et al, 2011).…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, these results were based on only 49 children, with no indication of maternal pre-pregnancy BMI or sex distribution. 28 Penders et al 10,29 reported that oral use of antibiotics during the first month of life resulted in decreased numbers of Bifidobacteria and B. fragilis group species, whereas the first mentioned have been found in higher numbers in lean subjects. Also, perinatal exposure to antibiotics, especially antibiotics of broad spectrum, have been associated to risk of asthma and atopic diseases in childhood, which was explained by long-term changes in the microbiotal composition early in life with lower counts of Bifidobacterium and higher counts of Bacteriodes.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota modulates various aspects of host physiology, including nutritional status, metabolism and immune-system maturation (Gill et al, 2006;Chow et al, 2010). Furthermore, the composition of the gut microbiota has been implicated in several human diseases, including type 1 diabetes (Wen et al, 2008), obesity Turnbaugh et al, 2006), asthma (Penders et al, 2007) and inflammatory bowel disease (Frank et al, 2007;Penders et al, 2007;Maslowski and Mackay, 2011). DNA sequencing technologies have enabled the profiling of microbial communities and their association with human health and disease (Eckburg et al, 2005;Gill et al, 2006;Ley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%